Do young men's reports of hormonal and long-acting contraceptive method use match their female partner's reports? - Elizabeth Karberg; Elizabeth Wildsmith; Jennifer Manlove; Makedah Johnson (Elsevier, 2019)
Objective: To assess whether young men's reports of hormonal and long-acting contraceptive methods match their female partner's reports. Study design: We analyzed a sample of 1096 heterosexual couples (aged 18-26) from the National Longitudinal Study of Adolescent to Adult Health Romantic Pair subsample. We compared male and female partner reports of hormonal/long-acting method use using class of method (hormonal/long-acting) rather than type (e.g., intrauterine device). Regression analyses linked men's reports of individual and relationship characteristics with alignment of reporting. Results: Sixteen percent of young men reported hormonal/long-acting method use at last sex differently than their female partner, that is, had a mismatched report. Men who had fewer lifetime sexual partners, had greater relationship satisfaction, believed their partner was monogamous and had a matched report of condom use at last sex were more likely to match their partner's report of hormonal/long-acting contraceptive use. Men living with children (from either partner) were less likely to have a matched report. Hispanic men were more likely to have a matched report than black men. Conclusions: Men are an increasingly important part of pregnancy prevention efforts. Pregnancy prevention and healthy relationship programs that incorporate communication skills may also indirectly improve young men's knowledge of their partner's contraceptive use and engagement in contraceptive decision making. Implications: Analyses showed that nearly two thirds of the 16% of young men that did not accurately report their partner's hormonal/long-acting method use at last sex underreport method use. Men at increased risk of misreporting may benefit the most from targeted pregnancy prevention programs. Keywords: Male reports, Hormonal/LARC contraceptive method